ANALISIS GERAK DAN KARAKTER RITUAL TARI DAKDENG PADA MASYARAKAT MELAYU DESA BAGAN SERDANG KABUPATEN DELI SERDANG - Cindi Soraya Dwi Putri Sibarani (Gesture: Jurnal Seni Tari, 2020)
ABSTRACT The results of the research based on the data obtained show that in the process of implementing the ceremony of rejecting the dance of Dakdeng dance present in the middle of the implementation becomes one of the important parts that must be carried out because the Dakdeng dance becomes a means of entry of supernatural spirits called Mambang which is the spirit of the ancestors of their descendents . Mambang's spirits entering the body of the family and community will dance during the process of rejecting reinforcements. There are differences in the movements and character of the Dakdeng dance between one dancer to the other. Because every Mambang who possesses the body of a family or a number of people who become dancers has a different character. Different character can be seen from Mambang Buaya who is angry when he feels disturbed, Mambang Knight is able to control emotions when there are other Mambang who unintentionally interfere, Blind Mambang has a sensitive mood, Mambang Leaders have a strict, hard and responsible nature, Mambang Penangis the loner and likes to cry, Mambang Macan is quiet and calm, Mambang Jelita is cheerful and encourages the other Mambang to dance, Mambang Galak is very angry when he sees the audience recording with his cellphone camera, Mambang Iba is gentle and a loner, Mambang Berdembah covers the genitals and is happy approaching with other Mambang spirits, Shy Mambang does not want to show his face in public and cover it with a scarf. Judging from the different character of Mambang, the movements performed are also different according to the wishes of each Mambang.                                                                                    Keywords: Movement, Character, Dakdeng Dance, Mambang.